Psychiatric Disorder in a Patient with Pituitary Tumor (Bangladesh Journal of Neurosurgery, 2019)
We report a case of a patient with pituitary tumor with psychiatric disorder, which posed a significant diagnostic dilemma and management challenge for the treating teams of neurosurgery, endocrinology and psychiatry. A more comprehensive endocrine work-up of atypical presentations can be considered in some cases. The criteria for determining when endocrine work should be considered should be investigated further.Bang. J Neurosurgery 2019; 9(1): 75-77